(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technological advancements refer to computerised financial systems which can be accesses by customers through a number of electronic banking platforms without getting to speak with bank employees. The key and secondary relationships of dimensions (factors) of Technological advancements and Customer Satisfaction is explored in this paper. On the basis of previous studies about the standardized service qualities of automated services and customer satisfaction, a uniform questionnaire was developed by defining and adapting attributes. Data was gathered from a sample of Indian Clients of banks. The collected data was split into two equal-sized sub-samples. An analysis of the Technology based service quality and customer satisfaction dimensions was conducted Using SPSS 21.0 software, exploratory factor analysis (EFA) was performed on half of the collected data. Confirmatory factor analysis (CFA) was performed on the remaining half of the data using AMOS 21.0 software to validate factor structure. The proposed model’s unidimensionality, reliability, and validity were empirically checked. AMOS 21.0 was also used to test hypotheses using structural equation modelling to investigate the relationship between Technological advancements and Customer Satisfaction (SEM). This research can aid bank management in determining customers’ quality perceptions of Technology based services, allowing banks to develop strategies to improve service quality and customer satisfaction.